2008
DOI: 10.1016/j.jtcvs.2007.08.055
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles of esophageal cancer

Abstract: Expression profiles of miRNA distinguish esophageal tumor histology and can discriminate normal tissue from tumor. MicroRNA expression may prove useful for identifying patients with Barrett esophagus at high risk for progression to adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
280
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(303 citation statements)
references
References 38 publications
(27 reference statements)
20
280
2
1
Order By: Relevance
“…MiR-21 has been confirmed to be overexpressed in many malignancies such as gastric cancer (Chan et al, 2008), pancreatic cancer (Roldo et al, 2006), hepatocellular cancer (Meng et al, 2007), colon cancer (Slaby et al, 2007), breast cancer (Iorio et al, 2005), prostate cancer (Volinia et al, 2006), brain tumor (Chan et al, 2005), cholangiocarcinoma (Meng et al, 2006), lung cancer (Markou et al, 2008), esophageal cancer (Feber et al, 2008), head and neck cancer (Tran et al, 2007), and ovarian cancer (Iorio et al, 2007). In addition, clinical significance of serum miR-21 expression in human cancers has been reported in recent investigations.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 has been confirmed to be overexpressed in many malignancies such as gastric cancer (Chan et al, 2008), pancreatic cancer (Roldo et al, 2006), hepatocellular cancer (Meng et al, 2007), colon cancer (Slaby et al, 2007), breast cancer (Iorio et al, 2005), prostate cancer (Volinia et al, 2006), brain tumor (Chan et al, 2005), cholangiocarcinoma (Meng et al, 2006), lung cancer (Markou et al, 2008), esophageal cancer (Feber et al, 2008), head and neck cancer (Tran et al, 2007), and ovarian cancer (Iorio et al, 2007). In addition, clinical significance of serum miR-21 expression in human cancers has been reported in recent investigations.…”
Section: Discussionmentioning
confidence: 99%
“…28 The expression of miR-205 is highly specific for squamous epithelium, 29 and it has been shown to be downregulated in both esophageal adenocarcinoma and ESCC. 30 miR-205 has also been found to function as an oncosuppressor in breast cancer and to improve responsiveness to tyrosine kinase inhibitor therapies. 31 Furthermore, miR-224, miR-27a and miR-200a have also been associated with hepatocellular carcinoma, ESCC and ovarian cancer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The global miRNA expression analyses (hierarchical clustering and principal component analysis) showed that the expression profiles of the miRNAs differed between the cisplatin-sensitive and -resistant cell lines (Figure 2), and expression levels of 45 miRNAs were changed by more than fourfold in cisplatin-sensitive cell lines as compared with cisplatin-resistant cell lines (Supplementary Table 1). Subsequently, the expression levels of the 10 miRNAs that were selected according to the miRNA microarray data and literature search [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were validated by quantitative reverse transcription-PCR. This confirmed that miR-141, miR-21, miR-19b, miR-200a, miR-19a, miR-27a, miR-20a and miR-20b were expressed at significantly higher levels in the cisplatinresistant lines, and miR-205 and miR-224 at significantly lower levels than in the cisplatin-sensitive cell lines (Po0.05) (Table 1).…”
Section: Cisplatin-sensitive and -Resistant Human Escc Cell Linesmentioning
confidence: 99%
“…18 Although upregulated in ovarian, bladder and breast carcinomas, [19][20][21] miR-205 has been reported to be downregulated in oesophageal cancers. 22 Thus, miR-205 might act as a doubled-edged sword by targeting opposite functional genes, as one miRNA can target a dozen mRNAs, impacting many molecules …”
Section: Mir-205 Suppresses Tumor Growth In Vivomentioning
confidence: 99%